The Effect of Insurance Literation, Perceived Product Benefits, Trust in Insurance & Perceived Product Risk on Decision to Purchase Personal Insurance - Cynthia Sari Dewi (Jurnal Multidisiplin Madani, 2023)
In this study, it is suspected that there are several factors that can influence the intention to purchase personal insurance. These factors are consumer insurance literacy, perceived product benefits, trustworthiness in insurance, perceived product risk, and favorable attitude towards personal insurance, so this research was conducted to determine whether there is an effect of these variables on the intention to buy insurance. This study uses Structural Equation Modeling (SEM) analysis with AMOS 24 software, and the results of the analysis state that there is no influence between Consumer Insurance Literacy and Perceived Product Benefits, Belief in Insurance, and Perceived Product Risk. In addition, Perceived Product Benefits have no effect on Favorable Attitude to Personal Insurance, Trustful Belief on Insurance has an effect on Favorable Attitude to Personal Insurance, Perceived Product Risk has no effect on Favorable Attitude to Personal Insurance, and Favorable Attitude to Personal Insurance has an effect on Inclination to Purchase Personal Insurance